An experimental model to investigate the biomechanical determinants of pharyngeal mucosa coating during swallowing. (27th April 2018) - Mathieu, Vincent; de Loubens, Clément; Thomas, Chloé; Panouillé, Maud; Magnin, Albert; Souchon, Isabelle
Abstract: The development of innovative experimental approaches is necessary to gain insights in the complex biomechanics of swallowing. In particular, unraveling the mechanisms of formation of the thin film of bolus coating the pharyngeal mucosa after the ingestion of liquid or semi-liquid food products is an important challenge, with implication in dysphagia treatment and sensory perceptions. The aim here is to propose an original experimental model of swallowing (i) to simulate the peristaltic motions driving the bolus from the oral cavity to the esophagus, (ii) to mimic and vary complex physiological variables of the pharyngeal mucosa (lubrication, deformability and velocity) and (iii) to measure the thickness and the composition of the coatings resulting from bolus flow. Three Newtonian glucose solutions were considered as model food boli, through sets of experiments covering different ranges of each physiological parameter mimicked. The properties of the coatings (thickness and dilution in saliva film) were shown to depend significantly on the physical properties of food products considered (viscosity and density), but also on physiological variables such as lubrication by saliva, velocity of the peristaltic wave, and to a lesser extent, the deformability of the pharyngeal mucosa. The biomechanical peristalsis simulator developed here can contribute to unravel the determinants of bolus adhesion on pharyngeal mucosa, necessary both for the design of alternative food products for people affected by swallowing disorders, and for a better understanding of the dynamic mechanisms of aroma perception.